Dynamic Changes in the Gut Microbiome at the Acute Stage of Ischemic Stroke in a Pig Model - Jeon, Julie; Lourenco, Jeferson; Kaiser, Erin E.; Waters, Elizabeth S.; Scheulin, Kelly M.; Fang, Xi; Kinder, Holly A.; Platt, Simon R.; Rothrock, Michael J.; Callaway, Todd R.; West, Franklin D.; Park, Hea Jin (Frontiers in Neuroscience, 2020)
Stroke is a major cause of death and long-term disability affecting 7 million adults in the US each year. Recently, it has been demonstrated that neurological diseases, associated pathology and susceptibility changes correlated with changes in the gut microbiota. However, changes in the microbial community in stroke has not been well characterized. The acute stage of stroke is a critical period for assessing injury severity, therapeutic intervention, and clinical prognosis. We investigated the changes in the gut microbiota composition and diversity using a middle cerebral artery (MCA) occlusion ischemic stroke pig model. Ischemic stroke was induced by cauterization of the MCA in pigs. Blood samples were collected pre-stroke, 4 hours (hr), 12 hr, 1 and 5 days post-stroke to evaluate circulating pro-inflammatory cytokines. Fecal samples were collected pre-stroke, 1, 3, and 5 days post-stroke to assess gut microbiome changes. Results showed elevated systemic inflammation with increased plasma levels of tumor necrosis factor alpha at 4 hr, and interleukin 6 at 12 hr post-stroke, relative to pre-stroke. Microbial diversity and evenness were reduced at 1 day post-stroke compared to pre-stroke. Microbial diversity at 3 day post-stroke was negatively correlated with lesion volume. Moreover, beta-diversity analysis revealed a trending overall differences over time, with the most significant changes in microbial patterns observed between pre-stroke and 3 days post-stroke. Abundance of the Proteobacteria was significantly increased, while Firmicutes decreased at 3 days post-stroke, compared to pre-stroke populations. Abundance of the lactic acid bacteria Lactobacillus was reduced at 3 days post-stroke. By day 5, the microbial pattern returned to similar values as pre-stroke, suggesting the plasticity of gut microbiome in an acute period of stroke in a pig model. These findings provide a basis for characterizing gut microbial changes during the acute stage of stroke, which can be used to assess stroke pathology and the potential development of therapeutic targets.